Agroflorestas: do potencial conservacionista à análise de experiências no Sudoeste do Paraná - Leite, Maristela da Costa (2015)
In the capitalist mode of production, certain human activities such as conventional agriculture, forestry, intensive livestock, as well as urban expansion and industrialization, have been responsible for the degradation of natural resources. These processes lead to harmful consequences for ecosystem dynamics, such as the reduction of biodiversity (plant and animal), erosion and soil fertility loss, mass movements, siltation of waterways, among others. Currently, the difficulties of finding alternatives to provide the conservation of natural resources, food production, as well as the recovery of degraded areas, become challenges to be faced due to economic rationality established in capitalist society. The agroforestry can be considered an alternative to this process. Characterized by the cultivation of agricultural species with forest ones in the same space and time, they allow, when properly planned and managed, a viable proposal that can combine food production and environmental conservation, therefore, considered as a conservationist use of natural resources. The agroforestry become even more prominent when they become a type of use that can occupy the areas regulated by the Environmental Law. The two legal forms of the Forest Code (Permanent Preservation Areas and Legal Reserve) are generally considered untouchable areas without utility by owners of farms. However, considering some aspects of Law No. 12,651 / 2012 (current Forest Code), as well as resolutions number 369/2006, 425/2010 and 429/2011 of the National Council of Environment (CONAMA) and the Normative Instruction (No. 5 / 2009) of the Ministry of Environment, it is possible to manage these areas, for example through agroforestry induction. But for each of them (Permanent Preservation Areas and Legal Reserves) there are restrictions that must be considered. In theory, the agroforestry present themselves as a viable alternative and, considering that is possible its utilization in areas regulated by law, it was sought to discourse on this issue, linking theory and the analysis of practical experience of agroforestry implementation through a project of agroforestry implementation in southwestern Paraná region. Started in 2010 and developed by the non-governmental organization Associação de Estudos, Orientação e Assistência Rural (ASSESSOAR) in 14 municipalities, it was sought to analyze the results in Unidades de Produção e Vida Familiares (UPVFs) from the cities of Capanema, Coronel Vivída e Francisco Beltrão, considering what have been the potential, the difficulties and the challenges that are set for the development of agroforestry activity. The developed experience already demonstrates that, in the environmental aspect, the agroforestry have many advantages. Nevertheless, structural problems influenced the development of agroforestry areas, such as the choice of the site, the quality of seedlings, preparation of the area, management, technical assistance and the lack of manpower.